(3MGTjI GdCejQ Ydi TQM GdCRgQjIs - (3eMeO Hf eMeO Hf CMeO Hf YHO GdbGOQ Hf YHO GdYRjR GdSfHGhj GdGRgQj, GdCejQ , J (B1232 (3g` s; (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO,J (B905 (3g` s ((3YeQ CfSi GdHjQhJi s)
(3ChdgG (B:s
(3fMeOc Gddge ef aGYd EQJaYf ThGFH GdRhGd CeG HYO ajbhd eMeO Hf eMeO GdeOYh HGdCejQ (B: (3gPg JbGjjO Ydi TQM GdCRgQjI CQLh HaVd Gddg Cf JSQ GdhOhO hJQZe GdMShO s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG hMHjHfG eMeO GdfHi GdCei hYdi Bdg hUMHg hSde hcGf GdaQGZ SfI (B1264(3g` s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs